A Comparison of Urology Training Across Five Major English-Speaking Countries - Naik, Rishi (Curr Urol, 2020)
BACKGROUND: Urology is a rapidly evolving specialty, although wide variations exist between training programs in different countries. We aimed to compare the status of urology training in 5 English-speaking countries. MATERIALS AND METHODS: Features compared include the training pathway structure, training requirements, competition levels and the process of moving country for international medical graduates. RESULTS: Length of training varied considerably across countries, ranging from 5 years in the USA and Canada, to 7 years in Australia and New Zealand and 9 years in the UK. Ease of entering urology training for international medical graduates also varies, with the UK relatively easier compared to other countries. All countries encourage participation in research during training as well as completion of non-urology and urology specific surgical examinations. CONCLUSION: Following the Royal College of Surgeons Improving Surgical Training report, it is vital that the UK incorporates optimal elements of international programs in order to provide the best standards for trainees and world-class care in urology.